Method for uniformly dispersing multi-walled carbon nanotubes in cement-based material
Through orthogonal experiments and electron scanning microscope image processing technology, the problem of difficult to evaluate the degree of dispersion of multi-walled carbon nanotubes in cement-based materials is solved, and the uniform dispersion and performance improvement of multi-walled carbon nanotubes are achieved.
Patent Information
- Application Number
- CN202411309118.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art lacks direct and accurate methods to characterize the degree of dispersion of multi-walled carbon nanotubes in cement-based materials, resulting in large measurement errors and affecting the evaluation of material performance improvement.
By designing orthogonal experiments, combining electron scanning microscopy and image processing technology, backscattering images are used to analyze porosity, and a mathematical model between multi-wall carbon nanotube doping, fly ash doping and water-adhesive ratio is established to optimize the preparation parameters To achieve uniform dispersion of multi-wall carbon nanotubes, image processing is used using ImageJ software to improve the accuracy of dispersion evaluation.
An effective method is provided to characterize the dispersion degree of multi-wall carbon nanotubes in cement-based materials, reducing errors, finding the optimal preparation parameters to improve material performance, and ensuring the uniform dispersion of multi-wall carbon nanotubes .
Smart Images

Figure CN119161118A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of concrete materials, and in particular relates to a method for uniformly dispersing multi-walled carbon nanotubes in cement-based materials. Background Art
[0002] The positive effects of the incorporation of multi-walled carbon nanotubes (MWCNTs) on the mechanical and electrical properties of cement-based materials have been initially explored. However, the large aspect ratio and surface area of MWCNTs easily lead to self-agglomeration, especially in water systems where they are unstable and difficult to disperse. Characterizing the dispersion of carbon nanotubes in cement-based materials is of great significance for evaluating the application of MWCNTs in cement-based materials to improve material performance and revealing the enhancement mechanism of MWCNTs on cement-based materials from the nanoscale and microscale.
[0003] Currently, there is no direct quantitative characterization method for the dispersion of carbon nanotubes in hardened cement-based materials:
[0004] The main methods for directly measuring the dispersion degree of multi-walled carbon nanotubes in liquid systems are UV-visible spectral absorption measurement and Zeta potential measurement. The principle of UV-visible spectral absorption measurement is: according to Lambert-Beer's law, the absorbance of the suspension is linearly related to the concentration of particles completely dispersed in the solution. Higher absorbance means better dispersion of multi-walled carbon nanotube materials in the solution. However, when stray light inevitably appears, it will directly affect the accuracy of the test, thereby causing a large error in the characterization of the dispersion degree of carbon nanotubes in cement-based materials. The principle of Zeta potential measurement is: particles carry more negative charges (positive charges), and at this time have a higher potential, the repulsive force between particles is greater than the attractive force, the better the particle dispersion, the more stable the dispersion of the entire system. On the contrary, the less negative charge (positive charge) the particles carry, the lower their potential, and when the attractive force is greater than the repulsive force, the particles are prone to agglomeration and flocculation precipitation, resulting in worse dispersion of the entire system.
[0005] For the dispersion of carbon nanotubes in cement-based materials, most of them are indirectly reflected by testing the mechanical properties, fracture toughness, microstructure density, etc. of carbon nanotube-modified cement-based materials: the dispersion method is used to first characterize the dispersion degree of carbon nanotubes in the dispersion liquid, and then the mechanical properties and electromagnetic shielding efficiency are tested. Due to the improvement of conductivity by carbon nanotubes, the dispersion degree of carbon nanotubes in cement-based materials is indirectly characterized; the compression, flexural strength and fracture toughness tests are used to indirectly reflect the dispersion of carbon nanotubes in cement mortar, and the scanning electron microscope and mercury intrusion porosimetry are used to characterize the dispersion of carbon nanotubes in cement mortar; quantitative image analysis of backscattered electron microscopy and X-ray computer microtomography data sets is used to indirectly characterize the dispersion of carbon nanotubes in hardened cement-based materials by testing the microstructure density. Summary of the invention
[0006] In order to improve the mechanical and electrical properties of cement-based materials, the present invention provides a method for uniformly dispersing multi-walled carbon nanotubes in cement-based materials and a method for characterizing the dispersibility of multi-walled carbon nanotubes in cement-based materials.
[0007] The method for uniformly dispersing multi-walled carbon nanotubes in cement-based materials comprises the following steps:
[0008] S1: Design multiple groups of orthogonal experiments with multi-walled carbon nanotube content, fly ash content and water-binder ratio as independent variables.
[0009] S2: Prepare multi-walled carbon nanotube modified cement-based materials, hydrate, take samples, observe the slurry area using an electron scanning microscope, obtain a backscattered image, and obtain the porosity of the slurry area through image processing.
[0010] S3: Establish a mathematical model between the multi-walled carbon nanotube content, fly ash content, water-binder ratio and porosity, and use porosity minimization as the optimization indicator to obtain the optimal preparation parameters, that is, the optimal multi-walled carbon nanotube content, fly ash content and water-binder ratio.
[0011] S4: Substitute the optimal multi-walled carbon nanotube content, fly ash content and water-binder ratio into step S2 to obtain the measured value of porosity. If the error is ≤2% compared with the minimized porosity in step S3, it is considered that the optimal multi-walled carbon nanotube content, fly ash content and water-binder ratio are appropriate. Otherwise, repeat step S3.
[0012] Further, step S1 includes:
[0013] S11: Several groups of three-factor five-level design experiments, the three independent variables are multi-walled carbon nanotube content, fly ash content, and water-binder ratio, and each independent variable has five different values;
[0014] S12: Fix the fine aggregate and the coarse aggregate, and calculate the usage of cement, fly ash, carbon nanotubes and water in each group of concrete according to the value level of each group of variables in step S11.
[0015] Further, step S2 includes:
[0016] S21: preparing a multi-walled carbon nanotube dispersion;
[0017] S22: Stir each group of components thoroughly, pour into a mold, cure, take samples, observe the slurry area using an electron scanning microscope, obtain a backscattered image, and obtain the porosity through image processing.
[0018] Furthermore, in step S21, the mass ratio of multi-walled carbon nanotubes to deionized water is 1:100, the ultrasonic power is 120w, the ultrasonic frequency is 40kHz, the dispersion time is 2h, and the dispersion temperature is 25°C.
[0019] Furthermore, the backscattered image was processed using ImageJ software, and the inflection point of the grayscale histogram of the backscattered image was determined as the grayscale threshold that distinguished the pores from the original image and displayed them as black, thereby separating the pores therein.
[0020] The invention also provides a method for characterizing the dispersibility of multi-walled carbon nanotubes in cement-based materials.
[0021] The method for characterizing the dispersibility of multi-walled carbon nanotubes in cement-based materials comprises: sampling after hydration of the multi-walled carbon nanotube-modified cement-based materials, observing the slurry area with an electron scanning microscope to obtain a backscattered image, and obtaining the porosity of the slurry area through image processing.
[0022] Furthermore, the backscattered image is processed using ImageJ software, and the inflection point of the grayscale histogram of the backscattered image is determined as the grayscale threshold value for distinguishing the pores from the original image and displaying them as black, thereby separating the pores therein.
[0023] Beneficial effects:
[0024] The porosity measurement method is used to characterize the dispersion degree of multi-walled carbon nanotubes in cement-based materials, which provides a method to evenly disperse multi-walled carbon nanotubes in cement-based materials and provides a premise for exploring the performance improvement of cement-based materials by multi-walled carbon nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Backscattering image of the 15th group of multi-walled carbon nanotube-modified high-content fly ash concrete.
[0026] Figure 2 Binarized image after separation of pores in modified high-volume fly ash concrete.
[0027] Figure 3 Surface plot of the effects of multi-walled carbon nanotube content and fly ash content on the porosity of concrete with a high content of fly ash. DETAILED DESCRIPTION
[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are described in detail below with reference to the accompanying drawings, but they should not be construed as limiting the applicable scope of the present invention.
[0029] The present invention provides a method for uniformly dispersing multi-walled carbon nanotubes in cement-based materials and a method for characterizing the dispersibility of multi-walled carbon nanotubes in cement-based materials. Multi-walled carbon nanotubes with poor dispersibility and in agglomerated form are regarded as pores in a backscattered grayscale image. The pores in the slurry region of the multi-walled carbon nanotube-modified cement-based material are segmented by using a binarization process and a grayscale threshold segmentation method in image processing, and finally the porosity of the slurry region is determined. The porosity is used as an index to evaluate the dispersibility of multi-walled carbon nanotubes in cement-based materials. The smaller the porosity, the fewer agglomerated multi-walled carbon nanotubes in the cement-based material, that is, the better the dispersibility of the multi-walled carbon nanotubes in the cement-based material.
[0030] Example
[0031] 1. Raw materials and test plan
[0032] 1.1 Raw materials
[0033] The present invention adopts a large amount of fly ash concrete mixed with multi-walled carbon nanotubes to characterize its dispersion degree as an embodiment. The cementitious material includes P·II42.5 type cement and grade II fly ash. The chemical composition and ignition loss of the two are shown in Table 1. The fine aggregate is river sand with a maximum particle size of 4.75mm and a fineness modulus of 2.7. The coarse aggregate is 5-19mm continuously graded crushed stone. The aggregate reaches a saturated surface dry state before use. The water reducer adopts a polycarboxylic acid type high-efficiency water reducer. The purity of the multi-walled carbon nanotubes used is greater than 95%, the inner and outer diameters are 3-5nm and 8-15nm respectively, the length is 3-15um, and the specific surface area is greater than 250m 2 / g, density is 0.08g / cm 3 .
[0034] Table 1 Chemical composition of cement and fly ash (wt.%)
[0035]
[0036] 1.2 Mix design
[0037] The multi-walled carbon nanotube modified fly ash concrete with a large amount of fly ash was prepared by a central composite design with three factors and five levels. The three factors were: X1, multi-walled carbon nanotube content (%, mass fraction of cementitious materials); X2, fly ash content (%, mass fraction of cementitious materials); X3, water-cement ratio (W / CM), as shown in Table 2, and a total of 20 groups of concrete were obtained. There is a corresponding relationship between the numbers in Table 2 and Table 3. For example, the content of multi-walled carbon nanotubes, the content of fly ash and the water-cement ratio in the concrete numbered 1 meet the condition numbered 1 in Table 2, and the ratio of cement, fly ash, carbon nanotubes, water, fine aggregate and coarse aggregate meets the condition numbered 1 in Table 3.
[0038] Table 2 Parameter selection of multi-walled carbon nanotube modified high-volume fly ash concrete
[0039]
[0040]
[0041] The mix ratio of multi-walled carbon nanotube modified fly ash concrete with a large amount of addition is shown in Table 3 below.
[0042] Table 3 Mix ratio of high-volume fly ash concrete (kg / m 3 )
[0043]
[0044] 1.3 Test methods
[0045] The multi-walled carbon nanotube dispersion was prepared by ultrasonic dispersion. The multi-walled carbon nanotubes were ultrasonically dispersed in deionized water for two hours (ultrasonic frequency of 40 kHz, ultrasonic power of 120 w) to obtain a uniformly dispersed multi-walled carbon nanotube dispersion (1 g / L).
[0046] The fly ash-rich concrete was prepared by a laboratory mixer. Fly ash, cement, coarse aggregate, fine aggregate, water, and dispersion were mixed for 4 min. After mixing, the fresh concrete was poured into a 100mm*100mm*100mm mold. Three specimens were prepared in each group. All specimens were covered with a layer of plastic film and then cured at room temperature for 24 h. After that, the specimens were demoulded and placed in a curing box (temperature 22±2℃, relative humidity 98%) for curing until 28 days. The 15mm*15mm*15mm part of the center of the specimen was immersed in isopropanol solution to stop hydration. After the specimen was dried, it was immersed in low-viscosity epoxy resin. After the resin hardened, it was polished with coarse and fine oil-based diamond powder until the surface of the specimen was smooth enough. After polishing, the specimen was ultrasonically cleaned in anhydrous ethanol to ensure the cleanliness of the specimen surface before testing. Finally, the surface of the specimen was sprayed with gold.
[0047] The BSE images of the slurry area of each sample were obtained using a VEGA3 XMU model TESCAN specification scanning electron microscope in high vacuum mode. 50 slurry areas were randomly selected from the observation surface for photography. The acceleration voltage was 30 kV, the working distance was 10-15 mm, the magnification of each image was 1500 times, the resolution was 768×858 pixels, and the scanning time for each sample was 60 s.
[0048] 2. Test results
[0049] 2.1 Porosity of multi-walled carbon nanotube-modified fly ash concrete
[0050] Figure 1 The backscattered image of the concrete paste modified with multi-walled carbon nanotubes and high content of fly ash is shown. In the backscattered image, the poorly dispersed and agglomerated multi-walled carbon nanotubes are equivalent to pores because of their black color.
[0051] In order to quantify the porosity of the interface transition zone of high-volume fly ash concrete, ImageJ software was used to process the backscattered image and separate the pores. During the separation process, the inflection point of the grayscale histogram of the backscattered image was determined as the grayscale threshold that distinguishes the pores from the original image and displays them as black. The separated binary image is shown in Figure 2. Figure 2 After the pores are separated from the image, the porosity of the slurry can be calculated based on the area fraction of the black pore area in the slurry area. The results are shown in Table 4. During the calculation process, 50 different slurry areas were selected for porosity calculation to reduce the error of a single image and improve statistical accuracy.
[0052] Table 4 Regional porosity of high-volume fly ash concrete paste (%)
[0053]
[0054] 2.2 Effects of different factors on the porosity of high-volume pulverized coal concrete
[0055] Taking the regional porosity (direct value) of concrete paste with high fly ash content as the dependent variable, a fitting formula between the significant factors and it can be established:
[0056] Y3=0.0420+0.0140X1-0.0124X2+0.0209X1 2 +0.0150X2 2 +0.0211X3 2 .
[0057] According to the fitting formula between the porosity of the paste region of high-content fly ash concrete and the significant influencing factors, a 3D visualization of the response surface of different influencing factors on the porosity of the paste region of high-content fly ash concrete can be obtained, which indicates the possible direction for the subsequent optimization of the porosity of multi-walled carbon nanotube-modified high-content fly ash concrete. Figure 3 The effects of multi-walled carbon nanotube content and fly ash content on the porosity of multi-walled carbon nanotube-modified high-content fly ash concrete are shown. Figure 3 The content of multi-walled carbon nanotubes and fly ash increased from 0 to 0.4% and from 50% to 70% respectively, and the water-binder ratio was fixed at 0.35. Figure 3 It can be seen that although there is no significant interaction between the content of multi-walled carbon nanotubes and the content of fly ash, the effects of both on the porosity of multi-walled carbon nanotube-modified concrete with a large content are not linear. When the water-binder ratio is taken to an appropriate value, under the premise of ensuring good dispersion of carbon nanotubes, the interface between fly ash and the matrix is improved by enriching carbon nanotubes around fly ash particles, and finally the performance of high-content fly ash concrete is improved.
[0058] 2.3 Optimization of porosity in the interface transition zone of high-volume fly ash concrete
[0059] According to the influence of different factors on the porosity of high-volume fly ash concrete, the three influencing factors were optimized with the goal of minimizing the regional porosity of the slurry of multi-walled carbon nanotube-modified high-volume fly ash concrete. During the optimization process, the weights of multi-walled carbon nanotube content, fly ash content, and water-binder ratio were the same, and the optimization results are shown in Table 5.
[0060] It can be seen from Table 5 that the optimal preparation parameters for obtaining the minimum porosity of multi-walled carbon nanotube modified high-volume fly ash concrete are: multi-walled carbon nanotube content is 0.11%, fly ash content is 66%, and water-binder ratio is 0.35. Under the optimal value, the predicted porosity of multi-walled carbon nanotube modified high-volume fly ash concrete is 32.8%.
[0061] Table 5 Performance optimization of multi-walled carbon nanotube modified high-volume fly ash concrete
[0062]
[0063] 2.4 Verification of the optimal solution for porosity of high-volume fly ash concrete
[0064] Based on the optimal preparation parameters, multi-walled carbon nanotube modified high-volume fly ash concrete was prepared. After 28 days of standard curing, the porosity of the slurry area was tested, and the measured value was 32.4%. The error between the predicted value and the measured value of the porosity of high-volume fly ash concrete was within 2%, indicating that the method of preparing modified high-volume fly ash concrete by controlling the amount of multi-walled carbon nanotubes, fly ash, and water-binder ratio, and characterizing the dispersion of multi-walled carbon nanotubes in cement-based materials by porosity is effective, and the preparation conditions for the best dispersion of multi-walled carbon nanotubes have been found.
Claims
1. A method for uniformly dispersing multi-walled carbon nanotubes in cement-based materials, characterized in that: The following steps are involved: S1: Design multiple groups of orthogonal experiments with multi-walled carbon nanotube content, fly ash content, and water-binder ratio as independent variables; S2: preparing multi-walled carbon nanotube-modified cement-based materials, hydrating them, sampling them, observing the slurry area using an electron scanning microscope, obtaining a backscattered image, and obtaining the porosity of the slurry area through image processing; S3: Establish a mathematical model between the content of multi-walled carbon nanotubes, fly ash content, water-binder ratio and porosity, and take the minimization of porosity as the optimization index to obtain the optimal preparation parameters, that is, the optimal content of multi-walled carbon nanotubes, fly ash content and water-binder ratio; S4: Substitute the optimal multi-walled carbon nanotube content, fly ash content and water-binder ratio into step S2 to obtain the measured value of porosity. If the error is ≤2% compared with the minimized porosity in step S3, it is considered that the optimal multi-walled carbon nanotube content, fly ash content and water-binder ratio are appropriate. Otherwise, repeat step S3.
2. The method for uniformly dispersing multi-walled carbon nanotubes in cement-based materials according to claim 1, characterized in that: Step S1 includes: S11: Several groups of three-factor five-level design experiments, the three independent variables are multi-walled carbon nanotube content, fly ash content, and water-binder ratio, and each independent variable has five different values; S12: Fix the fine aggregate and the coarse aggregate, and calculate the usage of cement, fly ash, carbon nanotubes and water in each group of concrete according to the value level of each group of variables in step S11.
3. The method for uniformly dispersing multi-walled carbon nanotubes in cement-based materials according to claim 1, characterized in that: Step S2 includes: S21: preparing a multi-walled carbon nanotube dispersion; S22: Stir each group of components thoroughly, pour into a mold, cure, take samples, observe the slurry area using an electron scanning microscope, obtain a backscattered image, and obtain the porosity through image processing.
4. The method for uniformly dispersing multi-walled carbon nanotubes in cement-based materials according to claim 3, characterized in that: In step S21, the mass ratio of multi-walled carbon nanotubes to deionized water is 1:100, the ultrasonic power is 120w, the ultrasonic frequency is 40kHz, the dispersion time is 2h, and the dispersion temperature is 25°C.
5. The method for uniformly dispersing multi-walled carbon nanotubes in cement-based materials according to claim 1, characterized in that: The backscattered image was processed using ImageJ software, and the inflection point of the grayscale histogram of the backscattered image was determined as the grayscale threshold that distinguished the pores from the original image and displayed them as black, thereby separating the pores therein.
6. A method for characterizing the dispersion of multi-walled carbon nanotubes in cement-based materials, characterized in that: include: After the multi-walled carbon nanotube-modified cement-based material is hydrated, a sample is taken and the slurry area is observed using an electron scanning microscope to obtain a backscattered image. After image processing, the porosity of the slurry area is obtained.
7. The method for characterizing the dispersion of multi-walled carbon nanotubes in cement-based materials according to claim 6, characterized in that: include: The backscattered image was processed using ImageJ software, and the inflection point of the grayscale histogram of the backscattered image was determined as the grayscale threshold that distinguished the pores from the original image and displayed them as black, thereby separating the pores therein.
